The companion of cellulose synthase 1 confers salt tolerance through a Tau-like mechanism in plants - Christopher Kesten (Nature Portfolio, 2019)
The Arabidopsis CC1 protein maintains microtubule array stability and cellulose synthesis during salt stress. Here the authors show that CC1 engages microtubules via an intrinsically disordered N-terminus that suggests it controls microtubule dynamics in a similar way to the mammalian Tau protein.